Pengembangan Sumber Daya Manusia Melalui Pelatihan Teknis Di Kantor Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kabupaten Takalar - Kamaluddin, Kamaluddin; Mahsyar, Abdul; Malik, Ihyani (Universitas Muhammadiyah Makassar, 2021)
This study aimed to determine the results of technical training held by BKPSDM Takalar Regency. This study used quantitative and descriptive quantitative research type. Data collection techniques were observation, questionnaires and documentation. The data were analyzed using quantitative descriptive statistics which were processed using the SPSS application. The population was 60 civil servants and the sampling technique used saturated sampling technique. The results of this study showed that systematic and planned eduaction and training indicators, continuous development, creation of learning organizations, training related to performance and management developmentand career planning were in a very good category. Also the technical training was needed for employees to support their careers and increase employee competence in the local government of Takalar Regency. Keywords: HR Development, Technical Training